Den danske Bonde-Praktika 1597-1804. Danske astrologiske bogtryk og deres udgrænsning i reformperioden - Madsen, Jakob Kortbæk (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2017)
Jakob Kortbæk Madsen: The Danish Bonde-Praktika 1597–1804. Danish astrological printings and their marginalisation in the agrarian reform period This article examines the history of the book Bonde-Praktika, a wide-ranging astrological handbook whose topics include general husbandry, weather prognostication, astrological nativities and medical advice. Originally of German origin (Bauern-Praktik, Bauernpraktik), the book was soon translated into a number of European languages. It thus represents the general trend of the spread of cheap astrological printings throughout much of Europe in the 16th and 17th centuries. The Danish Bonde-Praktika is unique however, not only when compared to the German original which appeared in many different versions, but also in the general context of the Danish book market, due to the fact that it saw practically no changes to either format or content: the 23 surviving editions, spanning the period 1597–1804, are essentially identical. In other words, the Danish Bonde-Praktika was a major success and remained popular among publishers and audiences alike for more than 200 years. Here I examine the book in the context of the other two most important vernacular examples of astrological printings in Denmark, the almanacs and prognostications (also known as practica). Seen together, these three genres paint a picture of a golden age for astrological printings in Denmark spanning the period c.1570–1633. Although the almanac (monopolized in 1636) contained a residue of astrological content until the 1830s, the Bonde-Praktika is the only truly astrology-based book to remain in print after the heyday, thus surviving what in recent years has been termed the marginalization of astrology. The last chapter of the article examines the process in which the long history of the Bonde-Praktika finally came to a halt. This process is seen in the context of the wide-ranging agrarian reforms that introduced major economic and cultural changes throughout the country in the decades around 1800. I suggest that this final marginalization of Danish astrological printings should be understood as an only partially intentional result of the reformers’ general wish to educate and enlighten the rural population. Although the Bonde-Praktika was in fact the target of several critics, the astrological worldview was at the same time indirectly supplanted through the introduction of new, astronomy-based theories which offered modern explanations of the nature of the celestial bodies.